2020
DOI: 10.1038/s41598-020-58116-1
|View full text |Cite
|
Sign up to set email alerts
|

PDZRN3 protects against apoptosis in myoblasts by maintaining cyclin A2 expression

Abstract: PDZRN3 is a PDZ domain-containing RING-finger family protein that functions in various developmental processes. We previously showed that expression of PDZRN3 is induced together with that of MyoD during the early phase of skeletal muscle regeneration in vivo. We here show that PDZRN3 suppresses apoptosis and promotes proliferation in myoblasts in a manner dependent on cyclin A2. Depletion of PDZRN3 in mouse C2C12 myoblasts by RNA interference reduced the proportion of Ki-67-positive cells and the level of Akt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…Previous studies reported that PDZRN3 and its E3 ubiquitin ligase domain serve an important role in ubiquitination function and in promoting cell differentiation (26,27), which confirms the hypothesis that it may be involved in promoting tumor progression. Following analysis of the public database TCGA, significant differences in PDZRN3 expression were identified in EC tissues.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies reported that PDZRN3 and its E3 ubiquitin ligase domain serve an important role in ubiquitination function and in promoting cell differentiation (26,27), which confirms the hypothesis that it may be involved in promoting tumor progression. Following analysis of the public database TCGA, significant differences in PDZRN3 expression were identified in EC tissues.…”
Section: Discussionsupporting
confidence: 76%